Filosofia e tragédia - Mendes, João Pedro (Classica - Revista Brasileira de Estudos Clássicos, 1989)
Both Philosophy and Tragedy are derived from ancient Greek religion. The former appeared when myths ceased to satisfy the curiosity and the desire of those thinkers who searched for a rational explanation of the origin of the universe; the latter, at the moment that were established cult performances of scenes from the life, the passion and the apotheosis of lhe god Dionysus in which were brougth out the problems and uncertanties of mankind. In order to search for the meaning of life the Dionysic elements of extreme extasy were joined to the Apollonian reason and dream. In tragedy one discusses the problem of existence by means of the fusion of mythos and logos (Pohlenz). The essence of trragedy lies in the confrontation of Man with destiny or, fellowing Claudel, with its antithesis: freedom.